2009
DOI: 10.1080/01421590802512896
|View full text |Cite
|
Sign up to set email alerts
|

Teaching basic life support algorithms by either multimedia presentations or case based discussion equally improves the level of cognitive skills of undergraduate medical students

Abstract: BLS teaching by either multimedia presentations or case based discussion equally improves the level of cognitive skills among medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The perceptions of the survey respondents presented here support these findings. Furthermore, instructional videos have been shown to be effective in teaching clinical skills like bedside procedures or resuscitation algorithms, either provided in classic fashion (Braslow et al, 1997;Carrero et al, 2009;Lenchus et al, 2011;Todd et al, 1998), or interactively embedded in virtual environments (de Vries and Handley, 2007;Lehmann et al, 2015;Ventre et al, 2011). As the participants in this survey underlined, constructive alignment with corresponding teaching activities is the key to successful implementation of learning activities (Biggs and Tang, 2007).…”
Section: Findings and Implications For Educational Practicementioning
confidence: 90%
“…The perceptions of the survey respondents presented here support these findings. Furthermore, instructional videos have been shown to be effective in teaching clinical skills like bedside procedures or resuscitation algorithms, either provided in classic fashion (Braslow et al, 1997;Carrero et al, 2009;Lenchus et al, 2011;Todd et al, 1998), or interactively embedded in virtual environments (de Vries and Handley, 2007;Lehmann et al, 2015;Ventre et al, 2011). As the participants in this survey underlined, constructive alignment with corresponding teaching activities is the key to successful implementation of learning activities (Biggs and Tang, 2007).…”
Section: Findings and Implications For Educational Practicementioning
confidence: 90%
“…The results of these studies have found PBL to be better[13141516] or comparable[217] to the traditional lecture-based method in terms of the improvement in the cognitive skills. PBL may not dramatically affect the knowledge scores but may significantly improve the knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The primary objective of teaching basic life support (BLS) and advanced cardiac life support (ACLS) is to learn the sequence of actions according to the American Heart Association (AHA) guidelines and to acquire the necessary skills. [23] In India, various surveys have shown lack of adequate knowledge of BLS/ACLS among medical students. [456] Therefore, it has been strongly recommended to incorporate BLS/ACLS teaching in undergraduate medical teaching curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these nine studies, four and five were performed in undergraduate and postgraduate anesthesia teaching, respectively. Amongst the four articles in undergraduate teaching, three assessed the student satisfaction with PBL in comparison to traditional lecture-based method [1, 8, 9], and one assessed the educational objectives accomplished with PBL [10]. The relevant clinical studies in postgraduate teaching compared PBL with traditional lecture-based method only in specific topics in anesthesiology like ethical aspects [11], preanesthetic assessment [12], intensive care [13], and continued medical education on air embolism [14].…”
Section: Literature Searchmentioning
confidence: 99%